Manufacturing Religion : the Discourse on Sui Generis Religion and the Politics of Nostalgia. - McCutcheon, Russell T. (Oxford University Press, 1997)
Offering a critique of traditional religion scholarship, this work focuses on multiple interrelated targets. It covers the history of religions as a discipline, and examines the ideological basis for, and service of, the "sui generis" argument.